Does Inhalation of Virgin Coconut Oil Accelerate Reversal of Airway Remodelling in an Allergic Model of Asthma? - Kamalaldin, N. A.; Sulaiman, S. A.; Yusop, M. R.; Yahaya, B. (Hindawi Publishing Corporation, 2017)
Many studies have been done to evaluate the effect of various natural products in controlling asthma symptoms. Virgin coconut oil (VCO) is known to contain active compounds that have beneficial effects on human health and diseases.The objective of this study was to evaluate the effect of VCO inhalation on airway remodelling in a rabbit model of allergic asthma.The effects of VCO inhalation on infiltration of airway inflammatory cells, airway structures, goblet cell hyperplasia, and cell proliferation following ovalbumin induction were evaluated. Allergic asthma was induced by a combination of ovalbumin and alum injection and/or followed by ovalbumin inhalation.The effect ofVCOinhalationwas then evaluated via the rescue or the preventive route. Percentage of inflammatory cells infiltration, thickness of epithelium and mucosa regions, and the numbers of goblet and proliferative cells were reduced in the rescue group but not in preventive group. Analysis using a gas chromatography-mass spectrometry found that lauric acid and capric acid were among themost abundant fatty acids present in the sample. Significant improvement was observed in rescue route in alleviating the asthma symptoms, which indicates the VCO was able to relieve asthma-related symptoms more than preventing the onset of asthma.